(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this essay, we discuss the history of calligraphy and handwriting, notable female calligraphers, the value of handwriting in both women’s and men’s education, and the handwriting learning process.